Evaluation of invasive and non-invasive methods for the diagnosis of Helicobacter pylori infection in symptomatic children and adolescents - Ogata, Silvio Kazuo; Kawakami, Elisabete; Patrício, Francy Reis Silva; Pedroso, Margareth Zabeu; Santos, Antonio Mario (São Paulo Medical Journal, 2001)
CONTEXT: Multiple diagnostic methods are available for the detection of Helicobacter pylori infection, but at present no single one can be used as the gold standard. OBJECTIVE: The aim of this study was to evaluate the diagnostic accuracy of 3 invasive and 2 non-invasive methods for detection of Helicobacter pylori infection in symptomatic children and adolescents. DESIGN: Prospective cohort study SETTING: Peptic Disease outpatients service, Discipline of Pediatric Gastroenterology, Universidade Federal de São Paulo / Escola Paulista de Medicina. PATIENTS: Forty-seven patients who underwent endoscopy because of dyspeptic symptoms. DIAGNOSTIC METHODS: Endoscopy with gastric biopsies for 3 invasive (rapid urease test, histology and culture) and 2 non-invasive methods (a commercial ELISA serology and 13carbon urea breath test - isotope ratio mass spectrometry) for detection of Helicobacter pylori infection. MAIN MEASUREMENTS: Sensitivity, specificity, positive and negative predictive values of each method and agreement and disagreement rates between the methods. RESULTS: Forty-seven patients [mean age, 11y9mo (SD 2y10mo), 27 female and 20 male]; 62% of them were Helicobacter pylori-positive. All methods agreed in 61%, and were negative in 21% and positive in 40%. The greatest concordance between 2 methods occurred between the invasive methods: histology and rapid urease test (89.6%) and histology and culture (87.5%). The greatest sensitivity, considering Helicobacter pylori-positive cases, for any combination of 3 or more tests, was achieved by the rapid urease test (S=100%), followed by histology, serology and 13carbon-urea breath test (S=93.1%) and lastly by culture (S=79.3%). The highest specificity was obtained by histology (100%) and culture (100%), followed by the rapid urease test (84.2%), serology (78.9%) and 13carbon-urea breath test (78.9%). CONCLUSIONS: Our results suggest that among invasive methods, an association between the rapid urease test and histology constituted the best choice for the detection of Helicobacter pylori infection. If results of histology and the rapid urease test are different, serology may be recommended.